Digestion of timothy silage and hay in reindeer - R. Moen; M. A. Olsen; Ø. E. Haga; W. Sørmo; T. H. Aagnes Utsi; S. D. Mathiesen (Rangifer, 1998)
Leafy timothy (Phleum pratense) silage (S), silage mixed with molasses (SM) and hay (H) were fed to nine male reindeer (Rangifer tarandus tarandus) calves in winter to investigate rumen function and digestion. Three calves were given S with 18.5% dry matter (DM), three were given SM (21.9% DM) and three were given H (85.0% DM). The content of water soluble carbohydrates (in % of DM) was 8.2% in S, 16.0% in SM and 8.5% in H. Median (range) daily DM food intake per kg BM was 12.9 (9-2-14.4) g in calves fed S, 19.0 (19-0-21.9) g in calves fed SM and 21.0 (19.2¬21.1) g in calves fed H. In vivo digestion of S and SM DM ranged from 78.5-83.1% compared to only 69-9-72.9% in calves fed H. In vitro DM digestion (IVDMD) of cellulose (median) incubated for 48 hours in rumen fluid was, however, significantly (F = 0.05) lower in calves fed S (24.4%) compared to calves fed SM (42.2%). Median IVDMD of cellulose (48 hours) in calves fed H was 36.4%. Total concentration of VFA (range) in the rumen fluid from reindeer fed H (99.7-113.6 mM) and was significantly (P<0.05) higher compared to animals fed S (57.7-85.9 mM) or SM (51.4-72.0 mM). Likewise, the pH of the rumen fluid (range) was significantly (P<0.05) lower in reindeer fed H (6.40-6.78) compared to animals fed S (6.97-7.30) or SM (6.79-7.27). Based on this study it is concluded that leafy timothy preserved as hay seems to be more suitable as emergency feed compared to silage. Supplementation of molasses to silage seems to stimulate food intake and ruminal cellulose digestion in reindeer. The lower intake of S compared to SM or H by reindeer may be explained by ruminal energy deficiency.